Lignin-Derived Carbon-Coated Functional Paper for Printed Electronics - (:unkn) unknown (AMER CHEMICAL SOC, 2021)
Next-generation printed electronics is required to be of high performance, cost-effective, multifunctional, sustainable, and environmentally benign. Herein, we report the manufacturing of a flexible carbon-coated paper for printed electronics ensuring the abovementioned requirements. The multifunctional carbon-coated substrate is achieved by employing copy paper, cellulose nanofibers (CNFs), and lignin-derived graphitic carbon as a base substrate, binder, and conductive pigment, respectively, using the scalable and simple Mayer rod coating and calendering methods. The pressure applied by the calendering led to a 96% decrease in electrical resistance for the carbon-coated paper. Wettability analysis revealed that the carbon layer is hydrophilic and capable of hydrogen bonding. The dielectric constant is obtained to be an order of magnitude less than that of the copy paper, indicating that the CNF binder between the carbon particles impedes the polarization mechanism. The impedance is measured as frequency-dependent and capacitive. The resistance, impedance, and dielectric values suggest that the carbon-coated paper is favorable for capacitive applications. Fabricating the flexible substrate with the biobased binder and conductive pigment introduces a significant step in sustainable and environmentally friendly printed electronics for future flexible capacitors, sensors, and wearable devices, especially for the applications where end-of-life disposal needs to be sustainable.
Keywords: printed electronics; paper electronics; lignin; carbon; coating; SOLID-STATE SUPERCAPACITORS; HYDROTHERMAL CARBONIZATION; NANOCRYSTALLINE CELLULOSE; POLYMER; TRANSPARENT; FABRICATION; GRAPHENE; AREA; NANOPARTICLES; ABSORPTION